Long Term Changes in Muscles around the Knee Joint after ACL Resection in Rats: Comparisons of ACL-Resected, Contralateral and Normal Limb - Mahiro Ohno, Hiroto Fujiya, Katsumasa Goto, Mitsutoshi Kurosaka, Yuji Ogura, Kanaka Yatabe, Takaaki Kudo, Hajime Kobayashi, Hisateru Niki, Haruki Musha (Journal of Sports Science and Medicine, 2017)
The purpose of this study was to investigate the long-term effects of anterior cruciate ligament (ACL) resection on the morphological and contractile characteristics of rectus femoris (RF) and semimembranosus (SM) muscles in both injured and contralateral hindlimbs in rats. Wistar male rats (8-week old) were used. Rats were divided into two groups; ACL-resected and (sham-operated) control groups. Furthermore, right and left limbs of rats in the ACL-resected group were assigned as ACL-resected and contralateral groups, respectively, at 1 day, 1, 4, and 48 weeks after ACL resection. No ACL-resection-associated changes in the mass of both muscles were observed 1 week after ACL resection. On the other hand, ACL-resection-associated reduction on mean fiber cross-sectional area (fiber CSA) in RF muscle lasted 48 weeks after ACL resection. Furthermore, ACL-resection associated increase in fiber composition of type I fiber in RF muscle in contralateral limbs. In addition, long-term effects of ACL resection were observed in both ACL-resected and contralateral limbs. Evidences from this study suggested that ACL resection may cause to change in the morphological (fiber CSA) and contractile (distribution of fiber types) properties of skeletal muscles around the knee joint in not only injured but also contralateral limb. Rehabilitation for quantitative and qualitative muscle changes by ACL resection may be required a special care for a long-term period.